Analisis Dampak Protes Black Lives Matter (BLM) Terhadap Penerimaan Sosial Di Amerika Serikat - Shandy Aura; Muhammad Zaenal Abidin (Universitas Islam Balitar, 2025)
This study examines the impact of Black Lives Matter (BLM) protests on social acceptance of racial justice principles in the United States. The protests became one of the largest social movements in modern American history, but normative analysis of their long-term influence on social structures and legal norms is limited. This study uses a normative qualitative method with a literature study approach, legal document analysis, and evaluation of secondary data from social media. The results of the study show that BLM protests have succeeded in raising public awareness of issues of racism, systemic discrimination, and the importance of social justice values. However, the level of social acceptance of anti-racism principles is still fragmented and influenced by people's social, economic, and political backgrounds. These findings underscore the importance of establishing more inclusive legal norms based on the value of racial equality as the foundation for sustainable social change in the United States.